Assessment of health and economic benefits of reducing fine particulate matter (PM2.5) concentration in Ho Chi Minh City, Vietnam - Tinh Huu Ho; Chinh Van Dang; Thao Thi Bich Pham; Supat Wangwongwatana (Elsevier, 2023)
Ambient fine particulate matter (PM2.5) is a growing issue in Ho Chi Minh City (HCMC), the most populous province in Viet Nam. Estimating the benefits of reducing PM2.5 levels has still been sparse in HCMC.The study used the Environmental Benefits Mapping and Analysis Program - Community Edition (BenMAP-CE) to estimate the health, and economic benefits in three controlling scenarios of annual average PM2.5 concentration in 2019 (28.9 µg/m3) rolling back to the World Health Organization's annual average Air Quality Guideline values of 5 µg/m3 (guideline value in 2021), and 10 µg/m3 (guideline value in 2005 which becomes Interim Target 4 of 2021 WHO Air Quality Guideline), and the Vietnamese annual average standard of 25 µg/m3.The annual average concentration of PM2.5 in 2019 was 28.9 µg/m3. Applying BenMAP-CE, the pooled number of avoided deaths of all causes was 3,785 (1,179-6,335), 3,195 (982-5,468), and 1,300 (384-2,386) for three scenarios, respectively. The economic benefits were $ 2.4 (0.8-4.1), $ 2.1 (0.6-3.5), and $ 0.8 (0.2-1.5) billion, using the Value of Statistical Life (VSL) of OECD (the Organization for Economic Cooperation and Development) and $ 3.7 (1.2-6.2), $ 3.1 (1.0-5.4) and $ 1.3 (0.4-2.3) billion, using the VSL of USEPA (the United States Environmental Protection Agency).The annual average PM2.5 concentration in HCMC exceeded the Vietnamese standard and WHO guidelines. Controlling PM2.5 showed massive benefits for health and the economy; thus, the city should have action plans for mitigating the PM2.5 pollution.